The Influence Of Students' Spirituality And Religiosity On The Use Of Shopee Paylater Facilities With Usury As A Moderating Variable - Fadhila Nur Kharisma; Devi Astriani; Fista Apriani Sujaya (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — To examine the influence of religiosity and spirituality of Faculty Of Economics and Business and Islamic education students on the use of Shopee PayLater. Research method— This study employs a descriptive verification approach with a quantitative method, utilizing a questionnaire as a survey tool. A sample of 359 respondents was selected using the Slovin formula, and analysis was conducted through a multiple regression model Result— The study found that both spirituality and religiosity levels have a significant negative effect on the use of Shopee PayLater. Additionally, student spirituality and religiosity significantly influence the use of Shopee PayLater, with usury acting as a moderating factor Conclusion— The findings indicate that higher levels of spirituality and religiosity among students lead to decreased usage of Shopee PayLater, highlighting the potential impact of ethical considerations in financial decision-making